Dignity of the Human Person - Loretan, Adrian (Philosophy and Canon Law, 2022)
The Vatican II fundamentally changed the ecclesiastical view towards the human person. Especially in Nostra aetate, Gaudium et spes, and Dignitatis humanae it strengthens the dignity of the human person and personal freedom as base for a world with equal rights for all mankind. Therefore, the council qualified discrimination of all kind as against God’s will. These statements have a huge impact on the necessary further development of theology and canon law.